P40 A comparison of the value of oxygen shunt studies and cardiac bubble echo as screening tools for pulmonary arteriovenous malformations in patients with suspected hereditary haemorrhagic telangiectasia. (16th November 2010) - Donaldson, JW; Pointon, K; Mathew, T; Fogarty, AW
Abstract : Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant genetic disorder associated with recurrent spontaneous epistaxis, mucocutaneous telangiectasia and visceral arteriovenous malformations (AVMs). Up to 30% of patients with HHT have pulmonary AVMs (PAVMs) which are associated with an increased risk of embolic stroke. Currently, with a sensitivity in excess of 98%, thoracic CT is the 'gold standard' for detecting PAVMs but involves a significant radiation exposure.1 Hence screening tools without a radiation burden such as oxygen shunt studies or cardiac bubble echo (CBE) are often considered as first line investigations for right-to-left shunts. With the recent introduction of CBEs to our hospital we collected data on patients who underwent both CBE and oxygen shunt studies. We looked retrospectively at 11 patients with suspected HHT (as defined by the Curacao criteria2 ) investigated over the last 5 years and aimed to determine the sensitivity and specificity of each screening test compared to thoracic CT (Abstract P40 Table 1 ). The oxygen shunt study had a sensitivity of 57% and specificity of 75%. CBE had 100% sensitivity (in five patients) but two studies were positive in the absence of detectable PAVMs on CT. Our data suggest that oxygen shunt studies are not sufficiently sensitive to be used as a screening tool for PAVMs. CBE is a useful initial screening test. A negative CBE combined with a negative chest x-ray has been shown to have a negative predictive value of 100% for PAVMs.3 This screening strategy is especially useful when the risk of CT irradiation is considered unacceptably high, for example in younger women. All patients with a positive CBE should undergo further imaging with thoracic CT to confirm the presence of PAVMs and to determine their size prior to consideration for embolisation therapy.